Chesterton's Epistemology: A Study in the Development of Newman's Doctrines. (April 2022) - Pickering, David
Abstract : This article situates G.K. Chesterton's work in relation to the theological epistemology of John Henry Newman. It studies the roles of reason, imagination, mystery, emotional knowledge, communal knowledge, and experience in Chesterton's epistemology, and the relationship between logical argument and narrative in his writing. The article attempts to demonstrate that Chesterton's work contains an implicit theological epistemology which in numerous respects parallels Newman's and argues that Chesterton developed Newman's epistemology in certain areas in the context of his work as an apologist. The article concludes with reflections on what Newman's influence on Chesterton may imply with regard to Chesterton's role as a hidden channel for Newman's influence on later writers.